0.9x-19=1.6x-26

Simple and best practice solution for 0.9x-19=1.6x-26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.9x-19=1.6x-26 equation:


Simplifying
0.9x + -19 = 1.6x + -26

Reorder the terms:
-19 + 0.9x = 1.6x + -26

Reorder the terms:
-19 + 0.9x = -26 + 1.6x

Solving
-19 + 0.9x = -26 + 1.6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1.6x' to each side of the equation.
-19 + 0.9x + -1.6x = -26 + 1.6x + -1.6x

Combine like terms: 0.9x + -1.6x = -0.7x
-19 + -0.7x = -26 + 1.6x + -1.6x

Combine like terms: 1.6x + -1.6x = 0.0
-19 + -0.7x = -26 + 0.0
-19 + -0.7x = -26

Add '19' to each side of the equation.
-19 + 19 + -0.7x = -26 + 19

Combine like terms: -19 + 19 = 0
0 + -0.7x = -26 + 19
-0.7x = -26 + 19

Combine like terms: -26 + 19 = -7
-0.7x = -7

Divide each side by '-0.7'.
x = 10

Simplifying
x = 10

See similar equations:

| x^2+20x-400=0 | | x+2x+(2x+8)=73 | | R^2=35+2r | | d-7=-4 | | -(3y+1)-(-2y-5)=1 | | X^2=-4-5x | | 2(7+x)-6=10 | | 3(9-3x)=9 | | 5x-45y=-30 | | 2y+13=5y+7 | | ((1-x)/2)-((x-2)/3)=-x/4 | | -4-2z=6 | | (2.5x)-(x)+4000=b | | 2x^2+20x-400=0 | | -0.3x^2+1.75x+1.25=0 | | 5+5+x=17 | | 24a/(x-24)=12a/30 | | x+y=(-4) | | -56=-2(5w+8)-(3w-12) | | 6(4x-2)=3(8x+8) | | 4m+2.3=9.2 | | -(7x-3)= | | 7(2x+3)-6=43 | | 9-2x=-7x+49 | | 8-(6x-4)=-48 | | 9+x^2=49 | | 7+2s-1=9s+24-5s | | 4(x+1)+5(x+6)= | | 9x-6(-2x+1)=-6 | | 8(2-x)=-16 | | y=-8x^9-7 | | 9/5x=1 |

Equations solver categories